Collaborative research on carbon reinforced concrete structures in the CRC/TRR 280 project. Issue 3 (29th June 2021) - Beckmann, Birgit; Bielak, Jan; Bosbach, Sven; Scheerer, Silke; Schmidt, Christopher; Hegger, Josef; Curbach, Manfred
Abstract: New materials allow new building designs and construction types. However, initial construction projects using the new materials show that traditional construction principles ‐ in the case of carbon reinforced concrete those derived from steel reinforced concrete ‐ are still being used. In other words, conventional materials are merely substituted. Only combined with intelligent construction strategies it is possible to exploit the full potential of innovative materials. Detached from established patterns of thought, the fundamentals for a new way of building with concrete are to be created in the frame of the Collaborative Research Centre Transregio (CRC/TRR) 280 project "Design Strategies for Material‐Minimised Carbon Reinforced Concrete Structures–Principles of a New Approach to Construction" at Technische Universität Dresden (TUD) and RWTH Aachen University. These are to be based on profound insights into the mechanical behavior of novel mineral structures. Innovative lightweight construction strategies and material composites reduce resource and energy consumption while maintaining high levels of usability, structural safety, and durability, while the aspirational esthetics make a valuable contribution to the culture of building. The long‐term research alliance of TUD and RWTH pools the excellent competencies, inspiring research into material‐minimized construction with mineral composites. The article highlights the research activities planned for the first period from July 2020 to June 2024.